A comparison of doctoral training in biomedicine and medicine for some UK and Scandinavian graduate programmes: learning from each other. Issue 5 (30th March 2019) - Williams, Anwen; Jones, Meriel G.; Jonsson, Roland; Harris, Robert A.; Mulvany, Michael J.
Abstract : Although the historical bases for graduate training in the United Kingdom (UK) and Scandinavia both stem from the original concept developed by von Humboldt, and both award a 'PhD degree', their paths have diverged. There are thus significant differences in the manner in which graduate training is organised. To analyse these differences, two UK graduate programmes (School of Medicine, Cardiff University; Institute of Integrative Biology, University of Liverpool) and two Scandinavian graduate schools (Faculty of Medicine and Dentistry, University of Bergen; Karolinska Institutet, Stockholm) completed a Self‐evaluation questionnaire developed by Organisation of PhD Education in Biomedicine and Health Sciences in the European System (ORPHEUS)). Analysis of the completed questionnaires shows differences concerning requirements for admission, the training content of PhD programmes, the format of the PhD thesis, how the thesis is assessed and the financial model. All programmes recognise that PhD training should prepare for employment both inside and outside of academia, with emphasis on transferable skills training. However, the analysis reveals some fundamental differences in the direction of graduate programmes in the UK and Scandinavia. In the UK, graduate programmes are directed primarily towards teaching PhD students to do research, with considerable focus on practical techniques. In Scandinavia, the focus is on managing projects and publishing papers. To some extent, the differences lead to a lack of full recognition of each other's theses as a basis for doing a postdoc. This paper describes the basis for these differences and compares the two approaches and points to areas in which there is, or might be, convergence. Abstract : We compared four United Kingdom (UK) and Scandinavian PhD programmes (School of Medicine, Cardiff; Institute Integrative Biology, Liverpool; Faculty of Medicine, Bergen; and Karolinska Institutet, Stockholm). Important differences concern admission criteria and the role of students in performing (UK) or managing (Scandinavia) their project. Also different emphasis regarding the thesis: UK, a bound thesis (200–300 pages); Scandinavia, published papers and a short review.